Prognostic Impact of Arterial Phase Hyperenhancement After Proton Beam Therapy for Untreated Solitary Hepatocellular Carcinoma - Hikaru Niitsu; Masashi Mizumoto; Yinuo Li; Masahiko Harada; Takuya Sawada; Masaaki Goto; Taisuke Sumiya; Keiichiro Baba; Takeshi Fujisawa; Masatoshi Nakamura; Toshiki Ishida; Takashi Iizumi; et al. (Cancer Medicine, 2026)
ABSTRACT Purpose To evaluate the significance of persistent arterial‐phase hyperenhancement (APHE) on contrast‐enhanced CT/MRI at 6 and 12 months after proton beam therapy (PBT) for hepatocellular carcinoma (HCC). Methods We retrospectively analyzed 108 patients with solitary HCC without vascular invasion who underwent definitive PBT as initial treatment between January 2008 and December 2020. APHE was assessed on contrast‐enhanced CT/MRI at approximately 6 and 12 months. Overall survival (OS), local control (LC), and progression‐free survival (PFS) were estimated using the Kaplan–Meier method. Associations between APHE and outcomes were evaluated using landmark analyses and Cox models. Results The median follow‐up time was 4.64 years. APHE assessment was available in 87 patients at 6 months and 89 patients at 12 months; APHE was observed in 28 (32.2%) and 26 (29.2%), respectively. At the 6‐month landmark, APHE was associated with worse subsequent OS and PFS, whereas LC did not differ significantly. At the 12‐month landmark, APHE was associated with worse subsequent LC and PFS and borderline worse OS. The 3‐year LC and PFS rates from the 12‐month landmark were 69.1% and 25.3% in patients with APHE versus 89.6% and 54.3% in those without APHE (LC: p = 0.015; PFS: p = 0.025). However, after adjustment for clinical and treatment‐related factors, APHE status was not independently associated with OS, LC, or PFS in the multivariate landmark analyses. Conclusion Persistent intratumoral APHE at 12 months after PBT was associated with an increased subsequent risk of local failure in landmark analysis, but was not an independent prognostic factor. Persistent APHE may warrant careful imaging follow‐up and clinical reassessment but should not be regarded as definitive evidence of viable tumor.